Superior immunogenicity of HCV envelope glycoproteins when adjuvanted with cyclic-di-AMP, a STING activator or archaeosomes. Issue 52 (15th December 2017) - Landi, A.; Law, J.; Hockman, D.; Logan, M.; Crawford, K.; Chen, C.; Kundu, J.; Ebensen, T.; Guzman, C.A.; Deschatelets, L.; Krishnan, L.; Tyrrell, D.L.J.; et al.
Abstract: Three decades after the discovery, hepatitis C virus (HCV) is still the leading cause of liver transplantation and poses a major threat to global health. In spite of recent advances in the development of direct acting antivirals, there is still a need for a prophylactic vaccine to limit the virus spread and protect at-risk populations, especially in developing countries, where the cost of the new treatments may severely limit access. The use of recombinant HCV glycoproteins E1E2 (rE1E2) in combination with the MF59, an oil-in-water emulsion-based adjuvant, has previously been shown to reduce the rate of chronicity in chimpanzees and to induce production of cross-neutralizing antibodies and cellular immune responses in human volunteers. To further improve neutralizing antibody responses in recipients along with robust T cell responses, we have explored the immunogenicity of different adjuvants when formulated with the HCV rE1E2 vaccine in mice. Our data show that cyclic di-adenosine monophosphate (c-di-AMP) and archaeosomes elicit strong neutralizing antibodies similar to those elicited using aluminum hydroxide/monophosphoryl lipid A (Alum/monophos. /MPLA) and MF59. However, both c-di-AMP and archaeosomes induced a more robust cellular immune response, which was confirmed by the detection of vaccine-specific poly-functional CD4 + T cells. We conclude that these adjuvants may substantially boost the immunogenicity of our E1E2 vaccine. In addition, our data also indicates that use of a partial or exclusive intranasal immunization regimen may also be feasible using c-di-AMP as adjuvant.